Rescuing, kidnapping, and criminalising. Migration containment in the Mediterranean. (22nd March 2021) - Garelli, Glenda; Tazzioli, Martina
This work investigates the government of migration from the angle of containment arguing that borderwork increasingly focuses on smuggling activities to achieve migration containment goals. The paper looks at three recent evolutions in the politics of containment in the central Mediterranean, and particularly in the corridor connecting Libya and Italy. First, we look at the practice of blocking migrants at sea upon rescue, what we call the politics of migrant kidnapping. Second, we study the statecraft of civil society into a smuggling organisation by policy - what we call the smugglerisation of civil society - by looking at governments' actions against those who rescue migrants whose boats are in distress. Finally, we look at how smuggling networks are made part of border enforcement practices. The paper shows how migration containment is enforced through multiple spatial tactics that block migrants at sea, hamper independent actors' search and rescue operations and target smuggling networks.